2022
DOI: 10.54386/jam.v24i4.1835
|View full text |Cite
|
Sign up to set email alerts
|

Multistage wheat yield prediction using hybrid machine learning techniques

Abstract: Wheat being highly affected by the weather, adverse weather drastically reduces the wheat yield. Model was developed for multi stage wheat yield prediction by stepwise multi linear regression (SMLR), support vector regression (SVR), least absolute shrinkage and selection operator (LASSO) and hybrid machine learning LASSO-SVR and SMLR-SVR techniques. Wheat yield data and weather parameter for generating thermal and weather indices during different growth stage for more than 30 years were collected for study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Contrarily, it can assist farmers in determining what and when to cultivate and organize their harvest and storage (Chergui et al, 2020). Interestingly, inter-annual crop yield fluctuation is influenced by climate variability (Ray et al, 2015;Kukal and Irmak, 2018) Weather variables affect every crop differently during different developmental phases (Ji et al, 2007;Gupta et al, 2022). Sridhara et al, (2023) reported maximum temperature and relative humidity played a significant role in pigeon pea yield prediction and found that stepwise linear regression (SLR) was outperformed by support vector machine (SVM), random forest (RF), least absolute shrinkage and selection operator (LASSO), and elastic net (ENET).…”
mentioning
confidence: 99%
“…Contrarily, it can assist farmers in determining what and when to cultivate and organize their harvest and storage (Chergui et al, 2020). Interestingly, inter-annual crop yield fluctuation is influenced by climate variability (Ray et al, 2015;Kukal and Irmak, 2018) Weather variables affect every crop differently during different developmental phases (Ji et al, 2007;Gupta et al, 2022). Sridhara et al, (2023) reported maximum temperature and relative humidity played a significant role in pigeon pea yield prediction and found that stepwise linear regression (SLR) was outperformed by support vector machine (SVM), random forest (RF), least absolute shrinkage and selection operator (LASSO), and elastic net (ENET).…”
mentioning
confidence: 99%
“…Artificial neural networks (ANNs) are another method for estimating evapotranspiration adept at capturing non-linear relationships and complex patterns, making them suitable for modeling the intricate nature of evapotranspiration. Machine Learning models find applications in various fields, including yield prediction (Gupta et al, 2022;Saravanan and Bhagavathiappan, 2022). Setiya et al, (2022) used five distinct approaches-SMLR, LASSO, ELNET, Ridge regression, and ANN to explore the correlation between yield…”
mentioning
confidence: 99%